Modeling and Simulation of Patient Services at Public Health Poly Centers Dr. Soetomo Surabaya - Kusuma, Otniel Reza; Jusak, Jusak; Sunarto, Dewiyani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Puskesmas (Community Health Center) is a healthcare organization established by the government to reach the rural population in order to get health so that people can work without any illnesses. Health Center Dr. Soetomo has 3 poly namely general clinic, dental poly and poly child's mother. Within the general clinic there is a buildup solving patients in the waiting room, thereby reducing health center services to patients. In solving the above problems, the authors conducted several analytical processes such as modeling and testing of probability distributions, generating random numbers and perform process simulation, keluara of the simulation process is the number of patients served, waiting time between a patient and utilization of patient care for 30 days. The simulation results are given to the head of the health center Dr. Soetomo as information.